2022
DOI: 10.1371/journal.pone.0279132
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral risk modification for multiple sclerosis susceptibility detected across the Major Histocompatibility Complex in a multi-ethnic population

Abstract: The Major Histocompatibility Complex (MHC) makes the largest genetic contribution to multiple sclerosis (MS) susceptibility, with 32 independent effects across the region explaining 20% of the heritability in European populations. Variation is high across populations with allele frequency differences and population-specific risk alleles identified. We sought to identify MHC-specific MS susceptibility variants and assess the effect of ancestral risk modification within 2652 Latinx and Hispanic individuals as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…To date, genome-wide screening efforts to identify determinants of MS risk in populations of non-European ancestry have only involved modest numbers of participants, thus providing limited statistical power 8. Unsurprisingly, none of these studies has identified new genome-wide significant associations, however the single nucelotide polymorphisms (SNPs) associated with MS susceptibility in genetically European populations have shown concordant effects on risk in populations of South Asian, African, Hispanic and ancestrally mixed backgrounds 9–16. It is inevitable that many of the variants of relevance in MS will differ in allele frequency between populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, genome-wide screening efforts to identify determinants of MS risk in populations of non-European ancestry have only involved modest numbers of participants, thus providing limited statistical power 8. Unsurprisingly, none of these studies has identified new genome-wide significant associations, however the single nucelotide polymorphisms (SNPs) associated with MS susceptibility in genetically European populations have shown concordant effects on risk in populations of South Asian, African, Hispanic and ancestrally mixed backgrounds 9–16. It is inevitable that many of the variants of relevance in MS will differ in allele frequency between populations.…”
Section: Introductionmentioning
confidence: 99%
“…It is inevitable that many of the variants of relevance in MS will differ in allele frequency between populations. This will potentially result in differences in power to identify such variants in specific populations, emphasising the value of studying the genetic architecture of MS in diverse cohorts 16 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS is a complex disease influenced by both genetic and environmental factors. Different patterns of risk and clinical expression have been associated with differing ancestry among patients with MS 20,21 and ON. 22 For example, genetic markers of native ancestry are significantly associated with ON as the presenting clinical event in a large Hispanic cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Hispanic ancestry is a genetic admixture of mainly Native American/American Indian, European, and African ancestries 17 with differing proportions as a consequence of complex political, social, and migratory histories to regions. Genetic admixture differences within African American and Hispanic populations have been found to correlate with an individual’s risk of MS. 18 This highlights a central role for the inclusion of ancestry to complement future examinations where both global and local variant-specific ancestral risk modifications could influence prevalence or phenotypic differences across racial and ethnic groups. Several ongoing clinical trials that focus on underrepresented populations build on this observational data complementing race and ethnic self-identify with genetic data.…”
mentioning
confidence: 99%